Aurelia aurita as a Model for Ecotoxicologically Assessing Food Additives: 2-Methyl-1-phenylpropan-2-ol and 1-Phenylethan-1-ol - Borja Mercado; Borja Vila; Luis Roca-Pérez; Neus Duran-Giner; Rafael Boluda-Hernández; Oscar Andreu-Sánchez (Toxics, 2025)
Industry currently generates numerous substances, such as food additives, whose environmental impacts, particularly in marine environments, remain inadequately assessed. This study employed Aurelia aurita for the first time as a model organism to evaluate the toxicity of such compounds. The main goal was to evaluate the toxicity of two food additives, 2-methyl-1-phenylpropan-2-ol (S1) and 1-phenylethan-1-ol (S2), on A. aurita ephyrae, comparing the results with other organisms representing different trophic levels, specifically the alga Phaeodactylum tricornutum and the crustacean Artemia salina. Acute toxicity tests were conducted on each organism. In A. aurita, S1 exhibited high toxicity (LC50 ≈ 10 mg/L), while S2 had lower toxicity (LC50 ≈ 80 mg/L). The pulsation frequency data for A. aurita revealed that S1 initially increased the pulsation rates at lower concentrations (maximum at 10 mg/L), followed by a significant decrease at higher concentrations. Conversely, S2 showed a steady decrease in pulsation rates up to 10 mg/L, with a slight increase at concentrations of 15, 20, and 25 mg/L. The results demonstrate varying sensitivities to the toxic effects of the two compounds across different trophic levels, with A. aurita ephyrae being the most sensitive. This suggests the potential efficacy of jellyfish as novel ecotoxicological models due to their heightened sensitivity, enabling the detection of lower contaminant concentrations in test samples. Further research is required to enhance the efficiency of ecotoxicological assays using this model.